INOVASI MEDIA PEMBELAJARAN CLAY BERBASIS NILAI ISLAMI DALAM MENINGKATKAN KREATIVITAS ANAK USIA DINI DI RA GUPPI KLESEM 2024/2025 - Defi Wulan Sri Rahayu; Septyana Tentiasih (LPPM IAD Probolinggo, 2025)
This study aims to explore the use of Islamic values-based clay as a learning medium to enhance early childhood creativity at RA GUPPI Klesem. Creativity is a crucial aspect that should be developed from an early age, involving imaginative thinking, problem-solving, and fine motor skills. Clay was chosen as an innovative medium due to its flexibility, ease of shaping, and potential for integration with Islamic values such as ethics and morality. Children were encouraged to create Islamic-themed shapes, such as Arabic letters, miniature mosques, and other religious symbols. This study employed a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation. The research subjects included teachers and children at RA GUPPI Klesem, with parents' involvement to support learning at home. The results show that clay significantly improved children's creativity, particularly in fine motor skills, imagination, and understanding of Islamic values. Children became more active, enthusiastic, and capable of producing creative, educational works. Moreover, the involvement of teachers and parents played a vital role in strengthening the effectiveness of learning. Thus, Islamic values-based clay learning media can be an innovative alternative to support creativity and character development in early childhood education. Keywords: Clay; Islamic Values; Creativit;, Early Childhood Education